Directions for Improving the Efficiency of Water Management Activities at the Microeconomic Level with the Help of Municipal-Private Partnerships (on the example of MP "Azovvodokanal") ("Journal "U". Economy. Management. Finance.", 2022)
The article considers the modern water management practice of SE "Azovvodokanal" and establishes the main parameters of water use. The authors justified the program of socio-ecological and economic optimization of water management activities of the priority water user of the Azov agglomeration using the mechanism of municipal-private partnership. The results of the study can be used by regional government authorities, local governments in the development of programs and projects of public-private and municipal-private partnerships in the areas of water supply and sanitation.
Keywords: water supply; water disposal; ecology; environmental management; economics; optimization; region; water resources; public-private partnership; concession